A comparative study of the NAART and WRAT4 Word Reading subtest to estimate reading level. Issue 1 (2nd January 2023) - Campbell, Elizabeth B.; Ergun, Gokce; Jackson, LaTrelle; Kim, Hyejin
Abstract: Patients are often asked to fill out paperwork in medical settings, but varying reading levels can affect the ability to self-report. By screening for reading level, clinicians can prevent potential patient confusion, frustration, and embarrassment. Clinicians can also avoid problems leading to misdiagnosis and providing materials that patients will not understand. The Wide Range Achievement Test – Fourth Edition (WRAT4) Word Reading (WR) subtest provides an estimation of word reading grade level as well as premorbid ability. The North American Adult Reading Test (NAART) only provides an estimation of premorbid abilities, but it is quick to administer and available in the public domain. By correlating these word reading measures (NAART & WRAT4 WR subtest), word reading level can be estimated by using the NAART alone. This project was a systematic replication of a study conducted by Jones et al. using a demographically-different sample of participants. Results indicate that NAART error scores and WRAT4 WR subtest raw scores were significantly correlated. Although the distributions of WRAT4 WR subtest raw scores from the Jones et al. study and the current study significantly differed, there was not a statistically significant difference between the proportion of predicted reading levels at/above or below fourth or fifth grade and actual reading levels at/above or below fourth or fifth grade. This finding suggests that the original regression equation created by Jones et al. can be applied to the current sample to accurately predict reading level classification.